Penguatan Budaya Belajar di SMA Melalui LSBS Berbasis Active Learning Sebagai Upaya Peningkatkan Kompetensi Guru dan Murid - Kusmawati, Ary (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study aims to describe the strengthening of collaborative, innovative, and reflective learning cultures in partner schools through the implementation of School-Based Lesson Study (SBLS) founded on active learning principles. A collaborative learning culture encourages cooperation in sharing ideas and achieving common goals; an innovative culture emphasizes the ability to create learning variations through different methods, models, and technologies; while a reflective culture focuses on self-evaluation to assess success and identify areas for improvement. The research was carried out in three stages: planning, implementation, and joint reflection. In the planning stage, schools formed SBLS teams, identified learning problems, determined topics and objectives, and developed observation instruments. The implementation stage involved applying active learning in classrooms, observing teacher and student behaviors, and collecting learning outcome data. The reflection stage consisted of presenting observation results, engaging in discussions, and developing follow-up plans for improvement. The findings show that SBLS based on active learning has a positive impact on strengthening the learning culture. For principals, this activity enhances data-driven leadership, collaborative culture, and learning quality. For teachers, SBLS improves pedagogical skills, professionalism, innovation, and reflective ability. For students, SBLS fosters critical thinking, empathy, mutual respect, and enthusiasm for learning. Institutionally, the program has led to increased teacher professionalism, the establishment of learning communities, an improvement in education report card scores up to 81.8%, and a higher number of schools achieving an “A” accreditation. Therefore, School-Based Lesson Study grounded in active learning is proven effective in strengthening collaborative, innovative, and reflective learning cultures in partner schools. Keywords: learning culture, collaborative, innovative, reflective, SBLS, active learning